Analisis Tindak Tutur Representatif Ketiga Ahli Hukum Tata Negara Sebagai Bintang Film Dokumenter Dirty Vote - Alyanisa Lintang Sekar Langit; Dhewi Safitri; Zulia Munna Khasanah; Sindi Awaliyah; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Rossi Galih Kesuma (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
YouTube has become an alternative medium for showcasing videos of varying lengths. Dirty Vote is one such long-form video, presented as a documentary film, available on YouTube. This documentary film is performed by three state law experts who also play the roles of researchers analyzing the content featured in the film. Starring Zainal Arifin Mochtar, Bivitri Susanti, and Feri Amsari, the film discusses political corruption that has occurred in Indonesia over the past few years. This research aims to analyze the speech acts performed by the three main stars of the documentary film "Dirty Vote" using representative speech act analysis with pragmatic theory. This research uses a descriptive research method with a qualitative technique. The data sources used in this research are the entire speech acts uttered by the three main actors in the documentary film Dirty Vote which discusses election practices in Indonesia. The data was collected through a free listening technique (SBLC) and additional writing techniques. The data analysis was conducted using a matching method with an informal data presentation method. Based on the conclusion, several types of speech acts were found, including stating, informing, complaining, recommending, demanding, reporting, explaining, giving, showing, mentioning, and speculating.